2002
DOI: 10.1038/sj.mn.7800123
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Regulation of the PD-L1 Immunoinhibitory Molecule on Microvascular Endothelial Cells

Abstract: These data show the expression of a novel B7-like molecule on murine ECs that is mediated by IFN-alpha, -beta, and -gamma, and suggest a potential pathway by which ECs may modulate T-cell function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
113
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 15 publications
6
113
2
Order By: Relevance
“…Consistent with our findings, IL-12 has been shown to regulated B7-H1 expression via IFN-γ in other cell types (Eppihimer et al, 2002;Cheng et al, 2007). Studies have suggested that B7-H1 expression was significantly increased on microvascular endothelial cells in vitro and in vivo after IL-12-challenge, but IL-12 was not effective at inducing B7-H1 expression in tissues of IFN-γ-deficient mice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our findings, IL-12 has been shown to regulated B7-H1 expression via IFN-γ in other cell types (Eppihimer et al, 2002;Cheng et al, 2007). Studies have suggested that B7-H1 expression was significantly increased on microvascular endothelial cells in vitro and in vivo after IL-12-challenge, but IL-12 was not effective at inducing B7-H1 expression in tissues of IFN-γ-deficient mice.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have suggested that B7-H1 expression was significantly increased on microvascular endothelial cells in vitro and in vivo after IL-12-challenge, but IL-12 was not effective at inducing B7-H1 expression in tissues of IFN-γ-deficient mice. These data showed that elevation of B7-H1 expression was induced by IL-12 through IFN-γ (Eppihimer et al, 2002). Comparable and similar data were observed in EAE mice.…”
Section: Discussionsupporting
confidence: 81%
“…The expression of PD-L1 on VECs has been related to the negative regulation of T cells. 17,18 In this study, we demonstrate that VECs not only express PD-L1, but also B7-1 (CD80), one of its receptors. The interaction between PD-1 and PD-L1 is well established as playing a vital role in controlling T-cell responses in a variety of contexts, from development to autoimmunity to microbial pathogenesis to tumor immunity.…”
Section: Discussionmentioning
confidence: 52%
“…15,16 Interestingly, PD-L1 also has been reported to be present on VECs under basal conditions, and the surface expression of PD-L1 on VECs can be increased by interferon-␣, -␤, and -␥. 17,18 However, the anti-angiogenic effect of PD-L1 has not been demonstrated to date. Here, we provide evidence for a novel regulatory function for PD-L1 in VEC proliferation in vitro and corneal angiogenesis in vivo.…”
mentioning
confidence: 99%
“…PD-1 has two known ligands: PD ligand (PD-L)1 (B7-H1) and PD-L2 (B7-DC). PD-L1 is expressed in a wide variety of tissues and by a number of different cell types, and its expression is upregulated by IFN-␥ (13)(14)(15)(16)(17)(18)(19). The expression of PD-L2 is much more restricted and appears to be limited to a subset of bone marrow-derived cells, including dendritic cells and macrophages (15,20).…”
Section: Pd-1:pd-l1 Interactionsmentioning
confidence: 99%